Long non-coding RNA LINC00265 promotes proliferation, apoptosis, and inflammation of chondrocytes in osteoarthritis by sponging miR-101-3p. (17th November 2021) - Zou, Hanlin; Lu, Chunde; Qiu, Jianjun
Abstract: Long non-coding RNAs (lncRNAs) play a part in a wide variety of diseases, including osteoarthritis (OA). This study was designed to investigate the biological role of lncRNA LINC00265 in OA and its underlying mechanisms. We examined the levels of LINC00265 and miR-101-3p using RT-qPCR, inflammatory factors using ELISA, and caspase-3, c-caspase-3, Bcl-2, Bax, and MMP-13 levels using Western blot in normal and OA chondrocytes, analysed the relationship between LINC00265 and miR-101-3p using bioinformatics analysis and luciferase reporter assays, performed loss- and gain-of-function analyses. The results showed that (1) LINC00265 expression was increased in OA chondrocytes, (2) si-LINC00265 inhibited OA chondrocyte apoptosis and inflammation, and (3) LINC00265 overexpression promoted normal and OA chondrocyte apoptosis and inflammation. Furthermore, we predicted and confirmed that miR-101-3p was a target of LINC00265. LINC00265 negatively regulated miR-101-3p in OA chondrocytes and LINC00265 promoted OA and normal chondrocyte apoptosis via miR-101-3p. Overall, lncRNA LINC00265 regulates chondrocyte apoptosis by acting as a sponge of miR-101-3p in OA.